The effect of education, training, and promotion on employee performance through job satisfaction in the inspectorate of Tanjungpinang City and Bintan District - Haryanto, Eko; Wibisono, Chablullah; Catrayasa, I Wayan (Goodwood Publishing, 2025)
Purpose: This study examines the relationship between education, training, and promotion on employee performance, mediated by job satisfaction. Research methodology: This study uses a quantitative research methodology involving survey questionnaires administered to employees in the Inspectorate of Tanjungpinang City and Bintan District. Results: This study is expected to show a positive relationship between education, training, promotion, and job satisfaction, with job satisfaction mediating their effect on employee performance. These findings aim to provide insights for organizations to enhance their HRM practices and optimize employee performance. Conclusion: Education, training, and promotion positively influence employee performance through the mediation of job satisfaction. Strengthening HRM strategies that enhance job satisfaction is essential for optimizing organizational outcomes. Limitations: Acknowledging constraints, this study recognizes limitations related to the sample size and geographical scope, which impact the generalizability of the findings. External factors beyond the control of this study may introduce variability. Contribution: This research enriches scholarly discourse by offering a nuanced understanding of how education, training, and promotion collectively impact employee performance through the lens of job satisfaction. Practical recommendations are provided for the organizational stakeholders.